Bodin on Sovereignty: Taking Exception to Translation?. Issue 2 (July 2015) - Keohane, Oisín
<x xml:space="preserve">Abstract</x> This article analyses the definition of sovereignty that Bodin provides in his 1576 Six livres de la république, which outlines sovereignty using French, Greek, Latin, Italian and Hebrew terms. It argues that, despite this attention to more than one language, Bodin wishes to present sovereignty as an unbound ideality beyond any and every language. Nevertheless, it is argued that Bodin in fact privileges the French souveraineté as that which sets up the analogical continuity between Greek, Latin, Italian and Hebrew. Accordingly, the article tracks the importance of French for Bodin in the wake of the 1539 Ordinance of Villers-Cotterêts, as well Bodin's claim that one of the 'true marks of sovereignty' is the power of the sovereign to change the language of his subjects. It ends by suggesting that the status of the exception in translation is not a species of sovereign exception, as Jean-Luc Nancy proposes, but a matter of linguistic justice.